A NOVEL SPECIES OF MALLOCYBE (INOCYBACEAE) FROM GILGIT-BALTISTAN, PAKISTAN - Hanza Ahmad Khan; Sobia Ilyas; Samina Sarwar; Abdul Razaq (Journal of Animal and Plant Sciences, 2026)
The genus Mallocybe has been recently delineated within the family Inocybaceae. Its recognition is based on distinctive macro-anatomical features as well as molecular phylogenetic evidence. Despite this advancement, the genus remains globally understudied. In Pakistan in particular, Mallocybe is underexplored, and its species diversity has yet to be systematically assessed. In this study, a fungal specimen was collected from Fairy Meadows (35.38685°N, 74.58416°E) at an elevation of approximately 3,300 meters in Gilgit-Baltistan. Comprehensive morpho-anatomical examination was conducted, alongside molecular characterization targeting the internal trnscribed spacer (ITS) region of nrDNA. The ITS sequence was amplified, sequenced, and analyzed phylogenetically to determine its taxonomic affiliation. This integrative approach led to the identification of a novel species, Mallocybe gilgitica, characterized by a depressed pileus with orange-brown fibrillose surface and dextrinoid basidiospores. Phylogenetic inference revealed a close affinity with Mallocybecrassivelata and Mallocybe leucoblema. This study reports a new Mallocybe species from Pakistan, identified through integrated morphological and molecular analyses, and highlights its valuable contribution to the fungal diversity of Pakistan.
Keywords: Fungal systematics; morphological traits; sequencing; South Asia